Feasibility, safety and outcomes of upgrading to left bundle branch pacing in patients with right ventricular pacing induced cardiomyopathy. Issue 6 (19th May 2022) - Rademakers, Leonard M.; Bouwmeester, Sjoerd; Mast, Thomas P.; Dekker, Lukas; Houthuizen, Patrick; Bracke, Frank A.
Abstract: Background: Right ventricular pacing (RVP) induces abnormal electrical activation and asynchronous ventricular contraction and leads to pacing induced cardiomyopathy (PICM) in 10%–20% of patients. Cardiac resynchronization therapy (CRT) utilizing biventricular pacing (BVP) is the recommended treatment. Left bundle branch pacing (LBBP) is a novel physiological pacing technique which may serve as an alternative to CRT. This study assessed feasibility and outcomes of LBBP delivered CRT in patients with PICM. Methods: Total 20 consecutive patients with PICM who received an upgrade of their pacemaker to LBBP were prospectively studied. Acute success rate, complications, functional and echocardiographic response, and hospitalization for heart failure within 6 months from implantation were evaluated. Results: LBBP was successfully delivered in all patients. Median duration of RVP before upgrade to LBBP was 3.8 years and the RVP was 99%. LBBP resulted in significant QRS narrowing (from 193 ± 18 ms to 130 ± 17 ms [ p < .001]), improvement in LVEF (from 32% ± 6 % to 47% ± 8% [ p < .001]) and NYHA class (from 2.8 ± 0.4 to 1.4 ± 0.5 [ p < .001]) at 6 months. No LBBP‐related complications occurred. No patients were hospitalized for heart failure or died. Conclusion: LBBP is feasible and safe in delivering CRT in PICM. Preliminary analyses demonstrated significant electrical resynchronization and favorable improvement in LV function and NYHA functional class at short term follow‐up. Data needs to be validated in large randomized controlled trials.